2017
DOI: 10.11613/bm.2017.017
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical external quality assessment of the Croatian Society of Medical Biochemistry and Laboratory Medicine and CROQALM: finding undetected weak spots

Abstract: IntroductionThe aim of this paper is to present results of first two years of preanalytical external quality assessment (EQA) in Croatia.Materials and methodsThis paper summarizes results from 6 rounds of preanalytical EQA during 2014-2016 in 161-175 Croatian laboratories (number ranged between cycles). EQA was designed as an online survey of the compliance with National recommendations for phlebotomy (NRP). Forty-seven questions in 5 categories are analyzed (materials and equipment, patient identification, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Given the risk associated with the use of reusable tourniquets and the quality of available evidence, we have graded this recommendation as 1A. Unfortunately, disposable tourniquets are not widely used, especially in some developing or non-developed countries [53]. Hospital management should be made aware of the risk associated with the use of reusable tourniquets and potential benefit of the use of disposable tourniquets for the safety of the patients and healthcare staff.…”
Section: Samplingmentioning
confidence: 99%
“…Given the risk associated with the use of reusable tourniquets and the quality of available evidence, we have graded this recommendation as 1A. Unfortunately, disposable tourniquets are not widely used, especially in some developing or non-developed countries [53]. Hospital management should be made aware of the risk associated with the use of reusable tourniquets and potential benefit of the use of disposable tourniquets for the safety of the patients and healthcare staff.…”
Section: Samplingmentioning
confidence: 99%
“…Laboratories in the UK and Ireland would reject 40% of results above the cut-off point automatically [29]. Nikolac et al [30] showed that 136 out of 159 laboratories (86%) would reject a potassium result in a sample with hemolysis of 0.5 g/L, while in our study, 72% of laboratories would reject a potassium test result in a sample with hemolysis of 1 g/L. The different actions taken by laboratories may indicate that they might apply less stringent quality criteria for some analytes to prevent rejection of test results, and therefore to a larger extent rely on local performance studies or apply cut-off points based on clinical needs [23,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…One such initiative was recently described in a study summarizing results from six rounds of preanalytical EQA during 2014-2016 in 175 Croatian laboratories, which showed that major critical spots during phlebotomy in Croatia were the lack of availability of safe-sharp needles, disposable tourniquets and glucose inhibitor tubes. The data may obviously differ from country to country, pointing to the need for more engagement of national professional associations in this area to assess the local specificities and requirements [56].…”
Section: Eflm Wg-pre Project: European Recommendation For Venous Bloomentioning
confidence: 99%